PENGARUH KOMBINASI BASIS PEG 400 DAN PEG 4000 PADA PEMBUATAN SEDIAAN SALEP EKSTRAK ETANOL BIJI MAHONI (Swietenia mahagoni (L). Jacq SEBAGAI ANTIBAKTERI TERHADAP Propionibacterium acne - Umi Hanifatun Nikmah; Galih Samodra (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Ointment preparations are semisolid preparations intended for topical use. Mahogany seeds (Swietenia mahagoni (L) Jacq) contain saponin compounds that have antibacterial activity, so they can be made into ointment formulations. This study aims to determine the stability of the physical properties as well as the antibacterial inhibition zone produced from the ointment preparation with the active ingredient of mahogany seed extract (Swietenia mahagoni (L)). Jacq) based on PEG 400 and PEG 4000. Physical properties were tested for 6 cycles of storage at a temperature of 5 C and at a temperature of 45 C, seen from the organoleptic, homogeneity, pH, spreadability, adhesion and viscosity. The results were analyzed using One Way ANOVA and paired t -test. The results of the One_ Way ANOVA test showed a significant difference <0.05 in the adhesion, spreadability and viscosity tests. The results of the paired t_test analysis showed that there was an effect of storage on the pH test with a value of <0.05, while the organoleptic test, homogeneity, viscosity, spreadability and adhesiveness had no effect during storage. Antibacterial tests on different formulas showed antibacterial activity on Propionibacterium acne. Before stability had an average inhibition zone at F1 (60%:40%) 12.76 mm, F2 (50%:50%) 10.58 mm and F3 (40%:60%) 8.74 mm, while after stability at F1 (60%:40%) 14.20 mm F2 (50%:50%) 12.44 mm, and F3 (40%:60%) 8.90 mm.